Regarding the article by V.V. Gordienko «On the nature of the Earth’s magnetic field» - Gintov, O.B. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2025)
V.V. Gordienko's article "On the Nature of the Earth's Magnetic Field" is aimed at criticizing plate tectonics. The author argues that paleomagnetic data are used to justify the mechanisms of lithospheric plate movement without sufficient grounds. However, numerous studies indicate the existence of subduction slabs, Benioff zones, coseismic movements, horizontal displacements, and stresses in the Earth's crust, confirmed by seismic tomography and GPS observations. Western scientists have long accepted plate tectonics as a fundamental concept, while the development of seismic tomography has shifted research focus toward plume tectonics. Both concepts are now considered parts of a unified convective process in the Earth's mantle. Regardless of the origin of the Earth's magnetic field, the existence of plate tectonics is proven by independent methods, including studies of crustal fracturing in Ukraine, which indicate its movement in the geological past.